(untitled) (LEARNing Landscapes, 2009)
I have been thinking about the over-arching theme of the poems and I think that they are all about literacy in some form or another."Straight Line" is about young children who are just entering into the world of words, and are taught in schools to be silent; "Stars" is about how we weave tales and songs from the night sky—and the world around us—to help us make meaning; and "The Paper Trail" is how ordinary words—in our everyday lives leave trails—even after we are gone.